The Estimation of Time since Death by Rule of Thumb method Applied to the Corpses Brought to the Mortuary, GGH, Guntur - Hussain , J A P; Rao , S M; Kumar , A L; Sugnan, B (Journal of Indian Academy of Forensic Medicine, 2023)
A physical change that may occur in a corpse after death would be heat exchange from the body to the surrounding environment. An attempt has been made by the investigators to estimate time since death by Rule of thumb method which takes into account the rate of fall of temperature. Atotal of 100 human corpses selected for the study. The study was conducted from January to March of the year 2022. It is very difficult to specify normal body temperature, as this value can vary considerably between individuals. Rectal temperatures in a group of healthy subjects can vary between 34.2 C- 37.6 C, with a mean 36.9 C. Rectal temperature is often referred to as deep central temperature, similar in value to that of brain, heart, lungs and abdominal organs.